Island effect in the shell phenotypic plasticity of an intertidal gastropod - Vasconcelos, J. (2020)
The pattern of shell shape variation in populations of the top shell, Phorcus sauciatus from Madeira Island (NE Atlantic) was analysed as a function of substrate type and wave exposure, using geometric morphometrics. We hypothesized that P. sauciatus shows morphological variations to inhabit contrasting environments. Highly significant differences in shell shape were found depending on both substrate type and coastal exposure. The most marked differences were found between exposed and sheltered environments. Rounded shells in exposed environments may be explained by physiological reasons, since larger muscles are needed to ensure attachment to substrate in areas subject to harsh conditions. On the other side, conically-shaped shells may accommodate a larger body but with a smaller foot, an adaptation to sheltered environments. Slight shape variations were also observed among substrates, mostly in the degree of differentiation of some whorls. Differences could be related to a particular use of habitat and/or to the degree of exposure to water current. These results suggest that P. sauciatus is locally adapted to varying coastal hydrodynamics and may be considered as a good model in studies on adaptations of fauna to certain climate change effects.